Implementation of Drug Logistics Management in Pharmaceutical Installations in Sigi Regency Health Office - Wandira, Bertin Ayu; Hermiyanty; Chikita, Marsanda (Media Publikasi Cendekia Indonesia, 2022)
Drug logistics management at the health office is one of the important aspects of the Public Health Center. The purpose of the study was to determine the planning, budgeting of procurement, storage, distribution, and elimination in drug logistics management at the Pharmacy Installation of the Sigi Regency Health Office. This type of research was qualitative with a case study approach. The informants in this study consisted of key informants (the Head of the Pharmacy Installation of the Sigi Regency Health Office), the usual informants (the Pharmacy Installation Staff of the Sigi Regency Health Office), and ordinary informants (the person in charge of managing the pharmacy installation at the Public Health Center). Data collection through triangulation techniques, including in-depth interviews, observation, and documentation using interview guidelines. The results showed that the implementation of drug logistics management at the Pharmacy Installation of the Sigi Regency Health Office in terms of planning, budgeting, procurement, storage, distribution, and elimination, was appropriate as it should be but still had some obstacles. So it is still necessary to improve the implementation of logistics management that is more effective and efficient. It is recommended that the coordination of the Sigi Regency Health Office and the Public Health Center is more optimal in the implementation of drug management.